2018
DOI: 10.1159/000492681
|View full text |Cite
|
Sign up to set email alerts
|

Noninfectious Inflammatory Response following Intravitreal Bevacizumab Injections: Description of a Cluster of Cases in Two Centers and a Review of the Literature

Abstract: Purpose: To report a cluster of high incidence of noninfectious inflammatory reaction shortly after bevacizumab injection. Methods: Data were collected from medical records of consecutive patients who underwent bevacizumab injections and presented with acute uveitis within 1–4 days. Results: All 7 patients were injected intravitreally with bevacizumab from different batches and presented with visual deterioration. One patient with anterior uveitis complained of pain. None had hypopyon. Three patients with vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Trivizki et al analyzed non-infectious inflammatory reactions after intravitreal bevacizumab injections in 2018 and concluded that 1.78% of patients with uveitis presented with anterior inflammatory cells after injection. 22 However, when classifying the degree of inflammation as mild-to-moderate, they did not include traces and defined the minimum level of cell count as 1+. Therefore, according to their classification criteria, the frequency of acute intraocular inflammation in our study would be 0.85%, which was less than that reported by Trivizki et al Wickremasinghe et al analyzed acute intraocular inflammation after monocular bevacizumab injection.…”
Section: Dovepressmentioning
confidence: 99%
“…Trivizki et al analyzed non-infectious inflammatory reactions after intravitreal bevacizumab injections in 2018 and concluded that 1.78% of patients with uveitis presented with anterior inflammatory cells after injection. 22 However, when classifying the degree of inflammation as mild-to-moderate, they did not include traces and defined the minimum level of cell count as 1+. Therefore, according to their classification criteria, the frequency of acute intraocular inflammation in our study would be 0.85%, which was less than that reported by Trivizki et al Wickremasinghe et al analyzed acute intraocular inflammation after monocular bevacizumab injection.…”
Section: Dovepressmentioning
confidence: 99%
“…In the pivotal nAMD trials for the approved anti-VEGF drugs, rates of IOI were reported to be ≤ 2.1% in ANCHOR and MARINA (any ocular inflammation of grade 3 or 4), ≤ 1.5% in VIEW 1 and VIEW 2, and ≤ 4.7% in HAWK and HARRIER [3][4][5][6]. IOI following anti-VEGF treatment often manifests as presence of cells in the anterior chamber or vitreous with reduced or blurred vision, which is typically treated with topical steroids and generally resolves without complication [2,[7][8][9][10][11][12]. Since FDA approval of brolucizumab in October 2019, there have been post-marketing reports of events of retinal vasculitis (RV) and retinal vascular occlusion (RO) associated with IOI following administration of brolucizumab [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several small series of intraocular inflammation after intravitreal injections of anti-VEGF presenting as uveitis have been described in the literature. 39 Non-infectious vitritis has been reported by Williams et al in 0.10% after 66,356 bevacizumab injections, 0.02% after 26,161 ranibizumab injections and 0.16% after 8071 aflibercept injections. 40 A true immune reaction to the anti-VEGF drug itself might be the explanation for the sporadic cases in which a rechallenge does result in a recurrent uveitis event.…”
Section: Intraocular Inflammation and Endophthalmitismentioning
confidence: 97%